Exploration Involving the Community in Upgrading Water Intake in Kampung Bongol, Tamparuli, Sabah, Malaysia - Zakaria, Siti Nor Farhana; Simon, Minir; Bolong, Nurmin (International Journal of Integrated Engineering, 2023)
This research highlights the project of upgrading a water supply system for a rural area in Kampung Bongol, Tamparuli, Sabah, Malaysia. This village is approximately 60 km from Kota Kinabalu town centre and takes about two hours to drive. Despite far access to the main water distribution pipeline, it is also a geographical challenge surrounded by mountains. However, the village is primarily situated near the existing catchment area. The previously developed setup for the community water distribution in this village is a traditional method using improper tools, systems, and facilities, which potentially causes water shortage issues for the villagers, especially during drought. To overcome this problem, a sustainable design of a mini dam and the usage of a ramp pump to distribute water were designed and built in this study. Combining these two elements can fulfill the storage distribution tank in a short time and supply clean water to the residents. Moreover, the 2-inch Polyvinyl chloride (PVC) ramp pump in this study has reduced the operational cost and zero-emission fuel, making this design practical and sustainable with the aid of the villagers. Despite a tight financial source and locality design technical revision implementation, this upgrading water project was accomplished within 4 months with community direct involvement. At the end of this project, the water distribution network using the designed system is successfully installed and supply water to the 200 villagers.